A Review on Relation between Entrepreneur and Innovation - Parul Mittal (AG Volumes, 2022)
As a consequence of the increased intensity of the competition, an increasing number of company owners are beginning to discuss the possibility of inventing novel techniques. What precisely do we mean when we use the word “innovation,” and why is it so important for those who run their own companies? As a result, one way to describe innovation is as the process of changing or upgrading an established practise. The term “innovation” refers to a one-of-a-kind resource that is available to company owners and gives them the ability to capitalise on possibilities brought about by movements in the market by developing new lines of business. An inventive entrepreneur is a businessperson who takes on challenging projects and creates one-of-a-kind goods to satisfy the requirements and preferences of the target audience in the target market. In a wide variety of diverse ways, the idea of innovation is very crucial to the game of entrepreneurship. Innovation businesspeople are those who are able to create and distribute unique products to customers, and they are given the moniker “innovative entrepreneurs.” The development of ideas that are helpful in the efficient management of businesses may be a benefit that can accrue to professionals who participate in creative entrepreneurship. If you are able to get your head around this concept, you will be well on your way to being away to being a successful businessperson. In this essay, we will first describe what it means to engage in innovative entrepreneurship, then investigate the many types of innovative entrepreneurship, and then investigate the skills that may enable an entrepreneur to be creative. The concepts of “innovation” and “entrepreneurship” are entirely distinct from one another and carry with them their very own specific implications. On the other hand, there is a remarkable relationship between innovation and entrepreneurialism, which may at times lead to misinterpretation. The major difference between innovation and entrepreneurship is that innovation refers to the process of introducing something new, while entrepreneurship refers to the act of beginning a new firm. This is the primary contrast between the two terms. It might be a novel approach to doing business, a new product, an innovative idea, or a new service. On the other hand, being an entrepreneur entails turning a wonderful idea into a successful business opportunity. This has its own set of challenges. Consequently, coming up with new ideas is the initial stage in every business endeavour. Another key difference between entrepreneurship and innovation is that the former does not include any element of risk, but the latter always does.